2003
DOI: 10.1038/oby.2003.130
|View full text |Cite
|
Sign up to set email alerts
|

Weekend Eating in the United States Is Linked with Greater Energy, Fat, and Alcohol Intake

Abstract: Results: This study's results indicate that statistically significant dietary intake differences occur for different days of the week but not for all age groups-nor for all nutrients. The average American, 2 years and older, consumes 82 kcal more per day on each weekend day (Friday through Sunday) than they do on weekdays (Monday through Thursday). These overall increases in dietary intake are significant for the overall sample and are largest for the 19-to 50-year-old age group; among this age group, the week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
136
6
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(171 citation statements)
references
References 7 publications
17
136
6
8
Order By: Relevance
“…In addition to protein, there was significantly greater variability in fat intakes on Sundays compared with weekdays for both males and females (Table 3), consistent with earlier research that reported variability in dietary intakes on weekends (Post et al, 1987;Haines et al, 2003). Sunday is the day of the week that is more likely to involve social activities around food, with less-structured food choices and mealtimes compared with weekdays.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition to protein, there was significantly greater variability in fat intakes on Sundays compared with weekdays for both males and females (Table 3), consistent with earlier research that reported variability in dietary intakes on weekends (Post et al, 1987;Haines et al, 2003). Sunday is the day of the week that is more likely to involve social activities around food, with less-structured food choices and mealtimes compared with weekdays.…”
Section: Discussionsupporting
confidence: 86%
“…Much of the Sunday lunch and dinner variability reflected the wide range of food choices typical for Australian weekend lifestyle practices in which various take-away meals and casual meals such as outdoor barbecues were common, whereas their consumption during weekdays was less prevalent. This observation was not unexpected as weekend changes to habitual weekday food choices are commonly observed among urban Western populations (Post et al, 1987;Haines et al, 2003).…”
Section: Discussionmentioning
confidence: 57%
“…Two studies demonstrated strong direct effects between portion sizes and energy intakes 38,39 . Seasonal variations in intakes were measured in countries differing considerably in their 25 Total fat USA Shelf space occupied by healthy foods in stores Objective De Castro (1992) 26 Energy, total fat USA Number of people present during meal Subjective De Craene (1990) 27 Total fat Belgium Location of residence, marital status Subjective (both) Diehr (1993) 28 Total 31 Energy, total fat USA Weekend/weekday, season Subjective Hellerstedt (1997) 32 Total fat USA Psychological demands, job latitude, job strain Subjective Johansson (1999) 33 Total fat Norway Location of residence, household income Objective (both) McCann (1990) 34 Energy, total fat, saturated fat USA Period of high/low workload Objective Morland (2002) 35 Total fat, saturated fat USA Whether or not there were the following food stores in the residential area:…”
Section: Resultsmentioning
confidence: 99%
“…Objective (all) † Supermarkets † Grocery stores † Full service restaurants † Fast-food restaurants Pomerleau (1997) 36 Total fat Canada Household income, source of income Subjective (both) Raynor (2004) 37 Total fat USA Availability of high-fat foods at home Subjective Rolls (2002) 38 Energy USA Portion size Objective Rolls (2004) 39 Energy USA Portion size Objective Rutishauser (1994) 40 Energy, total fat, saturated fat Australia Residing in a low or high socio-economic area Objective Shahar (2001) 41 Energy, total fat, saturated fat Israel Season (summer/winter) Objective Subar (1994) 42 Energy, total fat USA Season: summer or winter Objective Tarasuk (1999)43 Energy, total fat Canada Household food insecurity Subjective Van Staveren (1996) 44 Energy, total fat, saturated fat The Netherlands Season: summer or winter Objective Wardle (2000) 45 Energy UK Period of high/low workload Objective climate (USA, Israel and Europe), and mixed associations were seen 31,41,42,44 . Two studies found small differences in mean energy intakes between winter and summer, one found that intakes were marginally lower in winter among men 42 while another study among men found that energy intakes were slightly higher in winter 41 .…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27][28][29][30][31] The reported increase in energy intake that occurs over the weekend coupled with the reduction in physical activity reported on a Sunday in the overweight participants suggests that weekends are a time of positive energy balance in this at-risk group. It would be useful for future studies to compare daily energy intakes with daily step counts.…”
Section: Discussionmentioning
confidence: 99%